Diagnostic challenges of single plaque-like lesion paucibacillary leprosy - Raquel Rodrigues Barbieri; Anna Maria Sales; Ximena Illarramendi; Milton Ozório Moraes; José Augusto da Costa Nery; Suelen Justo Maria Moreira; Euzenir Nunes Sarno; Alice de Miranda Machado; Fernando Augusto Bozza (Memorias do Instituto Oswaldo Cruz, 2014)
The diagnosis of single-lesion paucibacillary leprosy remains a challenge. Reviews by expert dermatopathologists and quantitative polymerase chain reaction (qPCR) results obtained from 66 single-plaque biopsy samples were compared. Histological findings were graded as high (HP), medium (MP) or low (LP) probability of leprosy or other dermatopathy (OD). Mycobacterium leprae-specific genes were detected using qPCR. The biopsies of 47 out of 57 clinically diagnosed patients who received multidrug therapy were classified as HP/MP, eight of which were qPCR negative. In the LP/OD (n = 19), two out of eight untreated patients showed positive qPCR results. In the absence of typical histopathological features, qPCR may be utilised to aid in final patient diagnosis, thus reducing overtreatment and delay in diagnosis.